Treasure planet - Conli, Roy.; Musker, John.; Clements, Ron.; Edwards, Rob.; Gordon-Levitt, Joseph, 1981-; Murray, Brian, 1937-; Thompson, Emma.; Pierce, David Hyde.; Short, Martin, 1945-; Davis, Dane A.; Wincott, Michael, 1959-; Metcalf, Laurie, 1955-; et al. ([United States] : Walt Disney Home Entertainment ; Burbank, Calif. : Distributed by Buena Vista Home Entertainment, 2003)
Jim is a young man who grew up reading tales of pirates and adventures on the high seas, and longs for similar excitement in his own life. One day a dying man hands him a map and gives him a warning. Upon careful examination, Jim realizes the map charts the course to Treasure Planet, a distant world where hundreds of space pirates have stashed their loot. Jim is certain this is the adventure he's been dreaming of and sets out to find the fabled Treasure Planet.
Originally released as a motion picture in 2002.
Adapted from the novel "Treasure Island" by Robert Louis Stevenson.
English track: Dolby digital 5.1.
French track: Dolby digital 2.0 surround.
Spanish track: Dolby digital 2.0 surround.
Commentary 2.0.
Keywords: Animated films; Children's films; Feature films